1970
DOI: 10.1113/expphysiol.1970.sp002049
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis in the Foetal Guinea Pig

Abstract: Plasma total calcium levels have been studied in pregnant guinea pigs and their foetuses from 26 days of gestation to term. Between 28 days and 33-39 days the foetal plasma calcium falls from nearly the maternal level (9.6 mg/100 ml.) to 5-5 mg/100 ml. Thereafter the foetal plasma calcium rises, reaching the maternal level at term. No trend is found in the maternal levels. Foetal skeletal ossification was studied using an alizarin stain technique. Ossification centres appeared first in the clavicle, face and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Other possibilities are high calcium binding by fetal proteins or large quantities of citrate. The observed fall in fetal plasma calcium concentration between 16 and 18 days is coincident with the initial phase of skeletal calcification and resembles the findings in the guinea pig [Graham and Scothorne, 1970] [Graham andScothorne, 1970 and1971].…”
Section: Discussionsupporting
confidence: 52%
“…Other possibilities are high calcium binding by fetal proteins or large quantities of citrate. The observed fall in fetal plasma calcium concentration between 16 and 18 days is coincident with the initial phase of skeletal calcification and resembles the findings in the guinea pig [Graham and Scothorne, 1970] [Graham andScothorne, 1970 and1971].…”
Section: Discussionsupporting
confidence: 52%
“…At term the mammalian fetus has been reported to be hypercalcemic (1-4) and hyperphosphatemic (5-7), conditions which developed over a period of time in the final stages of gestation (10)(11)(12)(13). The present report confirms the gradual buildup of calcium and phosphorus in fetal blood and demonstrates, in addition, that as circulating levels of these elements rise, blood pH falls.…”
Section: Administration Of Ammonium Chloride or Sodium Bicarbonate Tosupporting
confidence: 90%
“…The difference in serum calcium between mother and fetus may, in part, be explained by the observation that the circulating level of this element in the dam falls in the final stages of gestation (5, 8,9). In addition, in the many mammals investigated, the level of calcium in the blood of the fetus has been shown to increase as termination of pregnancy is approached (10)(11)(12). Finally, in the rat, fetal phosphatemia has been shown to parallel the rise in blood calcium in the last days before birth (13).…”
mentioning
confidence: 97%
“…In human studies it has been demonstrated that plasma Cae' and Ca levels decrease (27) while the serum iPTH increases (28) during the last trimester of pregnancy. In the guinea pig and rabbit the fetal plasma Ca level decreases significantly below the maternal level at approximately mid-gestation, corresponding in the time with the onset of fetal skeletal calcification; subsequently, the fetal plasma Ca concentration increases and exceeds the maternal level at the end of gestation (29,30). In this regard, the findings of Smith et al are important and pertinent to the discussion (26).…”
Section: Discussionmentioning
confidence: 79%